La huida ante el sí mismo - Baquedano Jer, Sandra (ARFIL y UNL, 2018)
In the existential analytic of Being and time, anxiety does not appear simply as a state-of-mind (Befindlichkeit), nor simply as a psychological phenomenon, but as something much greater. Indeed, anguish appears as a fundamental existentiale, that is, a basic state-of-mind (Grundbefindlichkeit). By experiencing it, what is revealed to Dasein is its very being, yet this same experience may also destabilize Dasein. It is then that Dasein looks for and strives to find an ontical security which leads it to flee from itself. Taking this search as a starting point, we will probe how, whilst on the one hand, anxiety has the essential capacity to reveal Dasein’s being, it nevertheless has, on the other hand, the power to drive Dasein in turn to the most absolute alienation from itself, even when it is striving to find the path which leads towards authenticity.